Mempelajari Pembuatan Tepung dari Buah Pepaya sebagai Bahan Baku Makanan - Nur Oktavia; Tamrin Tamrin; Winda Rahmawati; Sapto Kuncoro (abe.fp.unila.ac.id, 2023)
Papaya is one of the fruits that are liked in the community because of it has a sweet taste and rich in vitamin C. In Indonesia papaya is abundant and the price of it is relatively low so that papaya gets wasted easily. Therefore, it is necessary to process the product to extend the shelf life and increase the value-added papaya fruit. Papaya flour is a product of new innovations of flour from the fruit besides papaya flour is food processed products to increase the value-added agricultural produce. In this study used the temperature treatment and type of papaya, with successive research procedures namely taking papaya fruit, peeling, slicing, soaking, drying, grinding, and sieving. The results showed that the temperature of drying can affect the moisture content of papaya flour, color, aroma, and vitamin C. The best quality of papaya flour is at 70°c, which is 23 with the desired color and aroma, resulting in an average water content of 4.9678% and vitamin C content that tends to be higher with a value of 420, 0667 (mg/100g). Drying with papaya type treatment does not significantly affect the moisture content of flour, color, aroma and vitamin C content. Keywords: Aroma, Drying, Flour, Papaya, Vitamin C